Depiction of a Postoperative Pseudomeningocele with Digital Subtraction Myelography - Phillips, C. Douglas; Kaptain, George J.; Razack, Nasser (American Journal of Neuroradiology, 2002)
Summary: Digital subtraction myelography is described for its utility in the detection of dural leaks associated with pseudomeningoceles. Although myelography, CT, and MR imaging have been described as effective means for diagnosing pseudomeningocele, this complicated entity can be difficult to diagnose.